People will talk the surprising science of reputation - Whitfield, John (Duckworth Overlook, 2012)
"How to get a good reputation--deserved or not!--and why we care what other people think. Why does a fish only bite another fish if no one else is watching? Why do people overshare online? Why do some people meet trivial insults with extreme violence? Why do so many gods have multiple eyes? In People Will Talk, science writer John Whitfield shows how reputation helps answer all of these questions, and more. What is the secret to getting a good reputation? Unfortunately, there's more to reputation than being a good person or being good at what you do. Your reputation belongs to other people, and it's created by what they say about you behind your back. You have a good reputation only if you have a strong social network--a large and close-knit network of friends, family, and allies--to spread good news about you and shout down ugly rumors. If you've ever wondered why we care about the lives of celebrities, why young men publicly upload to the Internet pictures of themselves engaged in drunken or dangerous antics, how to make the 'honor system' a little more widely honored, how to keep politicians honest, or what keeps gossip going, reputation will give you a clue. Almost from the moment we are born, we are trying to work out whom we can trust and trying to make others think the best of us. We carry on doing so throughout life, even when we don't realize it, every time we meet another person in business, friendship, or romance; every time we read celebrity gossip; and every time we tweak our Facebook profiles. Whether you're buying a car or selling one, looking for a job or hiring, asking someone out on a date or deciding whether to accept the invitation, reputation matters. Read People Will Talk and discover how to polish your own reputation, understand what you hear about others, and make the most of both"--
Keywords: Public opinion; Reputation